EXPLORING THE EMOTIONAL LANDSCAPE OF ENVIRONMENTAL ACTION: THE ROLE OF HOPE IN PRO-ENVIRONMENTAL BEHAVIOR - Julian Amriwijaya; Vidya Anindita (Adisam Publisher, 2025)
This study aims to explore the role of positive emotions, particularly hope, in fostering pro-environmental behavior amidst the increasingly alarming global ecological crisis. While many previous studies have highlighted the impact of negative emotions such as eco-anxiety on individual actions, constructive emotional aspects such as hope have received insufficient academic attention. Through a literature review of interdisciplinary studies from environmental psychology, behavioral science, and climate change communication, this study analyzes how hope can serve as a catalyst for sustainable environmental engagement. The findings suggest that hope is not simply a passive emotion but a psychological force that can shape perceptions, motivate action, and strengthen long-term commitment to sustainability. Furthermore, factors such as self-efficacy, social support, and positive narratives from the media or community leaders contribute to the formation of productive hope. This study emphasizes the importance of a balanced emotional approach in environmental education and communication strategies to create a psychological space that empowers individuals to act.